The Effect of Different Shapes of Confinement in Compression Zone on Beam's Ductility Subjected to Monotonic Loading. (2015) - Priastiwi, Yulita Arni; Imran, Iswandi; Nuroji
Abstract: This paper explains the experimental study on beams confined in compression zone with different shapes of extra confining reinforcement. The types of extra confining reinforcement considered are hoop reinforcement and cross ties. Three half-scale beam specimens (including the specimen with no extra confining reinforcement in the compression zone) have been tested under increasingly monotonic loading. The test results show that the presence of extra confinement in compression zone of beam section increase the ductility of the beam. However, no substantial increase are observed in the strength capacity of the beam specimens with extra confinement. In addition, more significant increase in ductility is obtained in the beam specimen with extra hoop in the compression zone than that with extra cross ties.